Hoc monimentum maesoleumque : les monuments funéraires dans le paysage des cités des Gaules et des Germanies romaines - Martial Monteil; William Van Andringa (Gallia)
This article introduces several new examples of funerary monuments discovered in six provinces of Roman Gaul and Germany. The antique sources show that the aim of these monuments, the most ostentatious of which are mausoleums, was to perpetuate the memory of the elites who built them. They are clearly differentiated from burials from a legal point of view, they present diverse forms and are installed on the outskirts of towns or in the countryside, as shown by the cases presented here. The earliest of them date back to the first period of the Augustan era, others were built in the fourth-fifth centuries, while a number of them disappeared with the construction of urban enclosures. However, some were dismantled long before this period, sometimes even as early as the 1st c. AD, suggesting earlier disuse, the stopping of commemorative rituals and possible legal formalities.